Breathing‐Based Meditation Decreases Posttraumatic Stress Disorder Symptoms in U.S. Military Veterans: A Randomized Controlled Longitudinal Study. Issue 4 (August 2014) - Seppälä, Emma M.; Nitschke, Jack B.; Tudorascu, Dana L.; Hayes, Andrea; Goldstein, Michael R.; Nguyen, Dong T. H.; Perlman, David; Davidson, Richard J.
<x xml:space="preserve">Abstract</x> Given the limited success of conventional treatments for veterans with posttraumatic stress disorder (PTSD), investigations of alternative approaches are warranted. We examined the effects of a breathing‐based meditation intervention, Sudarshan Kriya yoga, on PTSD outcome variables in U.S. male veterans of the Iraq or Afghanistan war. We randomly assigned 21 veterans to an active (n = 11) or waitlist control (n = 10) group. Laboratory measures of eye‐blink startle and respiration rate were obtained before and after the intervention, as were self‐report symptom measures; the latter were also obtained 1 month and 1 year later. The active group showed reductions in PTSD scores, d = 1.16, 95% CI [0.20, 2.04], anxiety symptoms, and respiration rate, but the control group did not. Reductions in startle correlated with reductions in hyperarousal symptoms immediately postintervention (r = .93, p < .001) and at 1‐year follow‐up (r = .77, p = .025). This longitudinal intervention study suggests there may be clinical utility for Sudarshan Kriya yoga for PTSD.